How the technology shock of the internet is radically changing the competitive dynamics of the online music market. (9th April 2007) - Graham, Gary; Hardaker, Glenn
This paper explores competition between firms in the online music market. It is evident from the analysis of our research dataset that firms acquire competitive advantage, by differentiating themselves on the range and quality of their music stock and through building social relational mechanisms with customers. The contribution of the work to electronic marketing and retailing is firstly, in the unique application, that it makes of Porter (1980, 1985, 2001) work on competitive strategies to the online music market and secondly, through its extension of generic competitive strategy concepts to the use of social relations as a strategy for differentiation and competitive advantage.